Evidence-based policy: A new approach to old problems - Józefowski, Bartosz (Journal of Public Governance, 2018)
The paper presents the origins and basic principles of the evidence-based policy (EBP) concept, introduces a brief analysis of this approach and highlights its key weaknesses. The author uses a ‘being, cognition, action’ approach, typical of many papers presented at the Kraków Circle seminar. EBP is heavily inspired by trends in modern medicine, and it became popular mainly due to Tony Blair’s speech. Unfortunately, many arguments show that it is difficult to use research results in public policy making. What is more, this approach runs the risk of abusing or even distorting in the long-term the incentive system among scientists. Although most of these problems have not been addressed properly by the EBP proponents, its high potential is undeniable, especially in the context of a growing number of success stories.